Annual Plan Proposals 1971-1972 Centrally Sponsored Schemes - Planning Commission (Planning Commission, 1971)
As per the All India Coordinated Rice Improvement Project sanctioned By I.C.A.R. e Regional Centre for Research in all aspects of rice was established at Pattsmbi from Jan. i960. The scheme has been sanctioned, by I.C.A.E. for four years from 1'967—63, The outlay is for continuing the cohere during
Government of Kerala Planning Department